1984
DOI: 10.1017/s0022172400064202
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of resistance of staphylococci grown in plasma to polymorph bactericidins

Abstract: SUMMARYThe mechanisms whereby staphylococcal strains grown in plasma assume increased resistance to polymorph bactericidins were investigated. Observations reported here showed that cultural conditions could determine the path of conversion to resistance. Staphylococcal strains and mutants lacking either free coagulase or clumping factor or both all showed enhanced resistance after 10 h incubation in plasma proteins, thus giving no clear indication that these factors were involved in the interactions. In fact,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
1984
1984

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The ease with which the slime layer was lost, especially by washing in saline broth, suggested that its acquisition was different from the mechanism of deposition of fibrin layer during growth in vivo in rabbits [7] or in vitro in plasma [8], since the only procedures that removed the surfacecovering in these cases were trypsin digestion or physical dissociation using 2 M potassium bromide [8]. Also, the similarity in the antibiotic sensitivity patterns of mucoid and non-mucoid organisms of the same strain showed that mucoid growth did not confer any additional resistance to antibiotics and hence that the resistance due to the mucoid layer was achieved by a mechanism which is different from the build-up of lipid in organisms grown in glycerol-broth [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…The ease with which the slime layer was lost, especially by washing in saline broth, suggested that its acquisition was different from the mechanism of deposition of fibrin layer during growth in vivo in rabbits [7] or in vitro in plasma [8], since the only procedures that removed the surfacecovering in these cases were trypsin digestion or physical dissociation using 2 M potassium bromide [8]. Also, the similarity in the antibiotic sensitivity patterns of mucoid and non-mucoid organisms of the same strain showed that mucoid growth did not confer any additional resistance to antibiotics and hence that the resistance due to the mucoid layer was achieved by a mechanism which is different from the build-up of lipid in organisms grown in glycerol-broth [2,3].…”
Section: Discussionmentioning
confidence: 99%